The criminal liability of Civil Servants and Non-Governmental Organizations in corrupt collaboration - Ananda Chrisna D. Panjaitan; Torang Fadly Panjaitan (Integritas: Jurnal Antikorupsi, 2026)
This article analyzes the expansion of the meaning of abuse of authority under Article 3 of Law Number 31 of 1999 concerning the Eradication of Corruption Crimes, as amended by Law Number 20 of 2001. The principal issues examined include: (1) whether omission or deliberate inaction by an civil servants may be legally qualified as an abuse of authority and (2) how joint liability between civil servants and NGO may be constructed within the framework of corrupt practices. Through this methodological framework, the doctrinal boundaries of abuse of authority and participation were systematically examined. The findings indicate that an omission by an civil servants who is under a legal duty to act may be qualified as an abuse of authority where such omission is carried out consciously and with the intent to benefit oneself or another person, and where it results instate financial loss. Within the context of collaboration, the doctrine of participation (medepleger) serves as the juridical foundation for attributing joint criminal responsibility between civil servants and NGO actors. It is concluded that the expansion of the interpretation of Article 3 must be undertaken cautiously within the confines of the principle of legality, while remaining responsive to the evolving patterns of collaborative corruption.